Literature and the human criticism, theory, practice - Mousley, Andy 1959- (London Routledge, 2013)
"Why does literature matter? What is its human value? Historical approaches to literature have for several decades prevailed over the idea that literary works can deepen our understanding of fundamental questions of existence. This book re-affirms literature's existential value by developing a new critical vocabulary for thinking about literature's human meaningfulness. It puts this vocabulary into practice through close reading of a wide range of literary works, from Shakespeare's A Midsummer Night's Dream to Don DeLillo's White Noise. Individual chapters discuss: Literature's engagement of the emotions; Literature's humanization of history; Literature's treatment of universals and particulars; The depth of reflection provoked by literary works; and Literature as a special kind of seeing and framing. The question at the heart of the volume, of why literature matters, makes this book relevant to all students and professors of literature." --Publisher's description.
Emotion -- History -- Universals and particulars -- Depth -- Beholding.
Quirong, Reginald Michael (Recommending faculty) : General Education / AHC
Includes bibliographical references and index.
Keywords: Literature -- Philosophy; Humanism in literature; Literature, Modern -- History and criticism -- Theory, etc